In vitro antimicrobial efficacy of two medical grade honey formulations against common high‐risk meticillin‐resistant staphylococci and Pseudomonas spp. pathogens. Issue 2 (5th December 2019) - Cremers, Niels; Belas, Adriana; Santos Costa, Sofia; Couto, Isabel; de Rooster, Hilde; Pomba, Constança
Abstract : Background: Antimicrobial resistance is a problem in human and animal healthcare. Honey may be used for its wound healing properties and antimicrobial effects. Objective: To investigate the antimicrobial activity of two commercially available medical grade honeys (MGHs) against Staphylococcus spp. and Pseudomonas spp. isolates. Methods and materials: Two formulations, MGH1 (40% w/v honey) and MGH2 (80% w/v Manuka honey), were tested in vitro for minimal inhibitory concentrations (MIC) and minimal bactericidal concentrations (MBC) against 11 Staphylococcus and 11 Pseudomonas isolates at low [1.5 × 10 4  colony forming units (cfu)/well] and high (1.5 × 10 6  cfu/well) concentrations of inoculum, representing systemic and cutaneous bacterial loads during infection, respectively. Results: MGH2 showed a lower MIC against staphylococci than MGH1, although this was not statistically significant. MGH1 had stronger bactericidal effects against staphylococci than MGH2, although this effect was statistically significant only at the higher bacterial concentration ( P  < 0.01). For Pseudomonas spp., MGH1 had significantly higher antimicrobial activity (both MIC and MBC) than MGH2 against all isolates tested and at both bacterial concentrations ( P  < 0.05). Conclusions and clinical importance: Both MGHs were effective in vitro against common cutaneous pathogens including meticillin‐resistant staphylococci and Pseudomonas species. The higher efficacy of the MGH1 formulation against Pseudomonas and its consistent effects against staphylococci, while containing only half of the amount of honey compared to MGH2, invites further investigation of the mechanisms and clinical applications of MGH1. Abstract : Background Antimicrobial resistance is a problem in human and animal healthcare. Honey may be used for its wound healing properties and antimicrobial effects.Objective To investigate the antimicrobial activity of two commercially available medical grade honeys (MGHs) against Staphylococcus spp. and Pseudomonas spp. isolates.Conclusions and clinical importance Both MGHs were effective in vitro against common cutaneous pathogens including meticillin‐resistant staphylococci and Pseudomonas species. The higher efficacy of the MGH1 formulation against Pseudomonas and its consistent effects against staphylococci, while containing only half of the amount of honey compared to MGH2, invites further investigation of the mechanisms and clinical applications of MGH1. Résumé: Contexte: La résistance antimicrobienne est un problème en santé humaine et animale. Le miel pourrait être utilisé pour ses propriétés de cicatrisation et ses effets antimicrobiens. Objectif: Etudier l'activité antimicrobienne de deux miels médicaux disponibles dans le commerce (MGHs) contre les souches de Staphylococcus spp. et Pseudomonas spp. Matériels et méthodes: Deux formulations, MGH1 (miel à 40% w/v) et MGH2 (miel de Manuka à 80% w/v), ont été testées in vitro pour la concentration minimale inhibitrice (MIC) et les concentrations minimales bactéricides (MBC) contre 11 souches de Staphylococcus et 11 Pseudomonas à faibles [1.5 × 10 4 colony forming units (cfu)/well] et hautes (1.5 × 10 6 cfu/well) concentrations d'inoculum, représentant respectivement une charge bactérienne systémique et cutanée au cours de l'infection. Résultats: MGH2 a montré une MIC plus faible que MGH1 contre staphylococci, bien que ce ne soit pas statistiquement significatif. MGH1 a des effets bactéricides plus forts contre staphylococci que MHG2, bien que cet effet ne soit statistiquement significatif qu'à la concentration bactérienne la plus élevée ( P < 0.01). Pour Pseudomonas spp., MGH1 avait une activité antimicrobienne significativement plus élevée (MIC et MBC) que MGH2 contre toutes les souches testées et aux deux concentrations bactériennes ( P < 0.05). Conclusions et importance clinique: Les deux MGHs étaient efficaces in vitro contre les pathogènes cutanés fréquents incluant les staphylocoques résistant à la méticilline et Pseudomonas . La plus grande efficacité de la formulation de MGH1 contre Pseudomonas et ses effets contre staphylocoques, alors que contenant moitié moins de mile que MGH2, implique la réalisation d'autres études des mécanismes et des applications cliniques de MGH1. Resumen: Introducción: la resistencia a los antimicrobianos es un problema en la salud humana y animal. La miel puede usarse por sus propiedades de cicatrización en heridas y por sus efectos antimicrobianos. Objetivo: investigar la actividad antimicrobiana de dos mieles de grado médico (MGHs) disponibles comercialmente frente a aislados de Staphylococcus spp . y Pseudomonas spp . Métodos y materiales: dos formulaciones, MGH1 (40% p/v de miel) y MGH2 (80% p/v de miel de Manuka), se probaron in vitro para detectar concentraciones inhibitorias mínimas (MIC) y concentraciones bactericidas mínimas (MBC) frente a 11 aislados de Staphylococcus y 11 aislados de Pseudomonas a bajas [1, 5 × 10 4 unidades formadoras de colonias (cfu)/pocillo] y altas (1, 5 × 10 6 cfu/pocillo) concentraciones de inóculo, que representan cargas bacterianas sistémicas y cutáneas durante la infección, respectivamente. Resultados: MGH2 mostró una menor MIC frente a estafilococos que MGH1, aunque esto no fue estadísticamente significativo. MGH1 tuvo efectos bactericidas más potentes frente a estafilococos que MGH2, aunque este efecto fue estadísticamente significativo solo a la concentración bacteriana más alta (P <0, 01). Para Pseudomonas spp ., MGH1 tuvo una actividad antimicrobiana significativamente mayor (tanto MIC como MBC) que MGH2 frente a todos los aislamientos probados y en ambas concentraciones bacterianas (P <0, 05). Conclusiones e importancia clínica: Ambas formulaciones de MGH fueron efectivas in vitro frente a patógenos cutáneos comunes, incluidos los estafilococos resistentes a meticilina y especies de Pseudomonas . La mayor eficacia de la formulación de MGH1 frente a Pseudomonas y sus efectos consistentes frente a estafilococos, aun teniendo solo la mitad de la cantidad de miel en comparación con MGH2, invita a una mayor investigación de los mecanismos y aplicaciones clínicas de MGH1. Zusammenfassung: Hintergrund: Die antimikrobielle Resistenz ist ein Problem bei der Gesundheitsvorsorge des Menschen und der Tiere. Honig könnte aufgrund seiner Wundheilungseigenschaften und antimikrobieller Wirkungsweisen Verwendung finden. Ziel: Eine Untersuchung der antimikrobiellen Aktivität zweier kommerziell verfügbarer medizinischer Honige (MGHs) im Einsatz gegen Staphylococcus spp. und Pseudomonas spp. Isolate. Methoden und Materialien: Zwei Formulierungen, MGH1 (40% w/v Honig) und MGH2 (80% w/v Manukahonig) wurden in vitro auf ihre minimale Hemmstoffkonzentration (MIC) und minimale bakterizide Konzentration (MBC) gegenüber Staphylococcus und 11 Pseudomonas Isolate getestet, wobei niedrige[1, 5 x 10 4 Kolonie‐bildende Einheiten (cfu)/Proberöhrchen] und hohe (1, 5 x 10 6 cfu/ Proberöhrchen) Konzentrationen von Inokulum eingesetzt wurden, was systemische bzw kutane bakterielle Belastungen während einer Infektion repräsentierte . Ergebnisse: MGH2 zeigte eine niedrigere MIC gegenüber Staphylokokken als MGH1, obwohl dieses Ergebnis nicht statistisch signifikant war. MGH1 zeigte eine deutlichere bakterizide Wirkung gegenüber Staphylokokken als MGH2, obwohl dieses Ergebnis nur bei höheren bakteriellen Konzentrationen statistisch signifikant war ( P < 0, 01). Bei Pseudomonas spp. zeigte MGH1 eine signifikant höhere antimikrobielle Aktivität (sowohl MIC als auch MBC) als MGH2 gegenüber allen getesteten Isolaten und bei beiden bakteriellen Konzentrationen ( P < 0, 05). Schlussfolgerungen und klinische Bedeutung: Beide MGHs waren in vitro gegen übliche Hautpathogene inklusive Methicillin‐resistenten Staphylokokken und Pseudomonas Spezies wirksam. Die höhere Wirksamkeit der MGH1 Formulierung gegenüber Pseudomonas und seine konstante Wirkung gegenüber Staphylokokken, obwohl es nur die halbe Menge an Honig im Vergleich zu MGH2 beinhaltete, laden zu weiterer Untersuchung des Mechanismus und der klinischen Anwendung von MGH1 ein. 摘要: 背景: 抗生素耐药性是人类和动物医疗保健中的一个问题。由于蜂蜜具有愈合伤口和抗菌作用, 因而值得使用。 目的: 研究现有市售的两种药用级别蜂蜜(MGHs)对葡萄球菌和假单胞菌分离株的抗菌活性。 方法和材料: 两种配方, MGH1 (40% w/v 蜂蜜) 和MGH2 (80% w/v Manuka 蜂蜜), 针对11个葡萄球菌和11个假单胞菌分离株, 体外测定其最小抑制浓度(MIC)和最小杀菌浓度(MBC), 选择培养液的低 [1.5 × 10 4 colony forming units (cfu)/well]和高 (1.5 × 10 6 cfu/well) 浓度, 分别代表感染期间全身和皮肤的细菌量。 结果: MGH2对葡萄球菌的MIC低于MGH1, 尽管这没有统计意义。MGH1对葡萄球菌的杀菌作用强于MGH2, 但这个结果仅在细菌浓度高时才有统计意义(P < 0.01)。对于假单胞菌, MGH1对所有被测菌株的抗菌活性(MIC和MBC)均高于MGH2, 且在两种细菌浓度下均高于MGH2 (P < 0.05)。 结论和临床意义: 在体外试验中, 两种MGHs对常见的皮肤致病菌, 包括耐甲氧西林葡萄球菌和假单胞菌均有效。与MGH2相比, MGH1配方对假单胞菌疗效更高, 且具有持续对抗葡萄球菌的作用, 但其蜂蜜含量仅为MGH2的一半。因此, MGH1的作用机制和临床应用有待进一步研究。 要約: 背景: 抗菌薬耐性は、人間および動物のヘルスケアにおける問題である。蜂蜜は、その創傷治癒特性および抗菌効果のために使用される場合がある。 目的: 本研究の目的は、2つの市販された医療グレードの蜂蜜(MGH)によるブドウ球菌およびシュードモナス属菌株に対する抗菌活性を調査することである。 材料と方法: MGH1(40%w / v蜂蜜)とMGH2(80%w / vのマヌカ蜂蜜)の2製剤に対し、それぞれ感染時の全身および皮膚細菌負荷を表す、低濃度[1.5×104コロニー形成単位(cfu)/ウェル]および高濃度(1.5×106 cfu /ウェル)のブドウ球菌および緑膿菌それぞれ11分離株に対する最小発育阻止濃度(MIC)と最小殺菌濃度(MBC)を in vitro でテストした。 結果: MGH2は、MGH1よりもブドウ球菌に対する低いMICを示したが、統計的に有意ではなかった。 MGH1はMGH2よりブドウ球菌に対して強い殺菌効果があったが、細菌濃度が濃い場合にのみ統計的に有意であった(P <0.01)。緑膿菌においては、MGH1は、試験した全分離株および両細菌濃度で、MGH2よりも抗菌活性(MICおよびMBCの両方)が有意に高かった(P <0.05)。 結論と臨床的重要性: 両MGHは、メチシリン耐性ブドウ球菌と緑膿菌を含む一般皮膚病原体に対して in vitro で効果的であった。 MGH2と比較し、半量の蜂蜜しか含まない一方で、緑膿菌に対するMGH1製剤の高い効力およびブドウ球菌に対する一貫した効果は、MGH1のメカニズムおよび臨床応用のさらなる調査をもたらす。 Resumo: Contexto: A resistência antimicrobiana é um problema na saúde humana e animal. O mel pode ser utilizado por suas propriedades curativas e efeitos antimicrobianos. Objetivo: Investigar a atividade antimicrobiana de dois méis medicinais (MGHs) comercialmente disponíveis contra Staphylococcus spp. e Pseudomonas spp. isolados. Métodos e materiais: Duas formulações, MGH1 (40% p / v mel) e MGH2 (80% p / v mel Manuka), foram testadas in vitro para concentrações inibitórias mínimas (MIC) e concentrações bactericidas mínimas (MBC) contra 11 Staphylococcus e 11 Pseudomonas isolados em baixas [1, 5 × 10 4 unidades formadoras de colônias (ufc) / poço] e altas (1, 5 × 10 6 ufc / poço) concentrações de inóculo, representando cargas bacterianas sistêmicas e cutâneas durante a infecção, respectivamente. Resultados: O MGH2 mostrou uma MIC menor contra estafilococos do que o MGH1, embora isso não tenha sido estatisticamente significativo. O MGH1 teve efeitos bactericidas mais fortes contra os estafilococos do que o MGH2, embora esse efeito tenha sido estatisticamente significativo apenas na maior concentração bacteriana (P <0, 01). Para Pseudomonas spp., O MGH1 apresentou atividade antimicrobiana significativamente maior (MIC e MBC) do que o MGH2 contra todos os isolados testados e em ambas as concentrações bacterianas (P <0, 05). Conclusões e importância clínica: Ambas OS MGHs foram eficazes in vitro contra patógenos cutâneos comuns, incluindo estafilococos resistentes à meticilina e espécies de Pseudomonas . A maior eficácia da formulação MGH1 contra Pseudomonas e seus efeitos consistentes contra estafilococos, embora contenha apenas metade da quantidade de mel em comparação com o MGH2, convida a uma investigação mais aprofundada dos mecanismos e aplicações clínicas do MGH1.